Accounting: Its Principles and Problems/Twenty-five years of Accounting Responsibility, 1911-1936/Financial Accounting: A Distillation of Experience. - Stone, Williard E. (The Accounting Review, 1973)
Abstract Reviews three books. "Accounting: Its Principles and Problems," by Henry Rand Hatfield; "Twenty-Five Years of Accounting Responsibility: 1911-1936," by George Oliver May; "Financial Accounting: A Distillation of Experience," by George Oliver May.